Antimicrobial activity of Brazilian copaiba oils obtained from different species of the Copaifera genus - Adriana Oliveira dos Santos; Tânia Ueda-Nakamura; Benedito Prado Dias Filho; Valdir F Veiga Junior; Angelo C Pinto; Celso Vataru Nakamura (Memorias do Instituto Oswaldo Cruz, 2008)
The antimicrobial activity of copaiba oils was tested against Gram-positive and Gram-negative bacteria, yeast, and dermatophytes. Oils obtained from Copaifera martii, Copaifera officinalis, and Copaifera reticulata (collected in the state of Acre) were active against Gram-positive species (Staphylococcus aureus, methicillin-resistant S. aureus, Staphylococcus epidermidis, Bacillus subtilis, and Enterococcus faecalis) with minimum inhibitory concentrations ranging from 31.3-62.5 µg/ml. The oils showed bactericidal activity, decreasing the viability of these Gram-positive bacteria within 3 h. Moderate activity was observed against dermatophyte fungi (Trichophyton rubrum and Microsporum canis). The oils showed no activity against Gram-negative bacteria and yeast. Scannning electron microscopy of S. aureus treated with resin oil from C. martii revealed lysis of the bacteria, causing cellular agglomerates. Transmission electron microscopy revealed disruption and damage to the cell wall, resulting in the release of cytoplasmic compounds, alterations in morphology, and a decrease in cell volume, indicating that copaiba oil may affect the cell wall.